Molecular Imaging of Prostate Cancer: PET Radiotracers - Jadvar, Hossein (2012)
OBJECTIVE: Recent advances in the fundamental understanding of the complex biology of prostate cancer have provided an increasing number of potential targets for imaging and treatment. The imaging evaluation of prostate cancer needs to be tailored to the various phases of this remarkably heterogeneous disease. CONCLUSION: In this article, I review the current state of affairs on a range of PET radiotracers for potential use in the imaging evaluation of men with prostate cancer.